A clearing-and-staining procedure for the study of the chondrocranium and other aspects of skeletal development in crocodilian embryos - Fernandez Blanco, María Victoria (2020)
Skull development has been of particular interest to crocodilian researchers, largely because their highly derived skulls have obscured homology of key phylogenetic characters. The chondrocranium has been of particular interest given its role in providing the substrate for endochondral ossification and the scaffold for dermal (intramembranous) ossification. Development of the skeleton in general and chondrocranium in particular has been studied via histology and contrast-enhanced computed microtomography (microCT), but clearing and staining of whole-mount specimens remains a relatively rapid and cost-effective means of generating adequate sample sizes. Historically, there have been many protocols for clearing and staining vertebrate skeletons that produce striking specimens with bluish cartilage and reddish bone within a relatively transparent body. However, application of this technique to crocodilians has been poorly described and standardized. Crocodylia is one of only two extant clades of Archosauria (Aves being the other), and thus the study of the development of the elements of crocodilian skeletons is crucial for evolutionary and paleontological studies. In this contribution, we describe a precise procedure for clearing and staining crocodilian embryos and young post-hatchlings, focusing on three species: Alligator mississippiensis, Caiman latirostris, and C. yacare. In brief, the steps include: initial preparation, bleaching, fixation, dehydration, cartilage and bone staining, clearing (with 0.5% KOH/glycerol series and enzymatic treatment), and storage. Using these procedures, we obtained specimens that provided clear discrimination of bony and cartilaginous anatomy, demonstrating the efficacy of this protocol for crocodilians, particularly with regard to elucidating the structure of the chondrocranium, which is illustrated here for three species.